PENGARUH DUKUNGAN KELUARGA MELAKUKAN PIJAT OKSITOSIN TERHADAP KELANCARAN ASI PADA IBU MENYUSUI - Dewi Andariya Ningsih; Innama Sakinah; Siti Rohmah Nur Aisyah; Syifa Fadhilah; Syarifatul Hasanah (LPPM Universitas Abdurrab, 2024)
ABSTRACT The important role of the family in the mother's ability to provide exclusive breastfeeding to her child is one factor. The mother gets full support so she can care for her child well. The external factor that most influences the success of exclusive breastfeeding is family support. Exclusive breastfeeding will not be successful if family support is lacking. Some breastfeeding mothers still have difficulty producing breast milk in the right way. Three-quarters of a dozen breastfeeding mothers were respondents in this study. Data collection was carried out through questionnaires, SOP sheets and observation sheets. Data analysis was carried out by considering research ethics and using editing, coding and tabulation. Analysis was carried out before and after intervention using the McNemar test. The aim is to find out how family support influences oxytocin massage for ease of breastfeeding. There is strong evidence that there is a substantial change in breastfeeding fluency between pretest and posttest, as shown by the findings of the McNemar test which produces a significance value (sig.) of 0.00. The operational area of ​​the Arjasa Community Health Center will be the research location from October 2022 to January 2023. Based on the Chi Square test findings, characteristics that can interfere with smooth breastfeeding do not show a significant relationship. It is recommended that more research be carried out to find out whether maternal massage significantly affects how well breast milk flows.